Clinical Characteristics and Long-Term Prognosis of Anti-LGI1 Encephalitis: A Single-Center Cohort Study in Beijing, China - Li, Tao-Ran; Zhang, Yu-Di; Wang, Qun; Shao, Xiao-Qiu; Lyu, Di-Yang; Lv, Rui-Juan (Frontiers in Neurology, 2021)
Background: This study aimed to analyze the clinical characteristics of anti-leucine-rich glioma-inactivated protein 1 (LGI1) encephalitis patients and investigate prognostic factors by using a large-sample and long-term follow-up cohort. Methods: The clinical data of 45 patients (29 males; mean age, 57.0 years) from May 2014 to August 2019 were collected. All patients were followed up by face-to-face interviews in the third month after discharge and then by telephone and/or face-to-face interviews every 6 months until November 2020. We evaluated each patient’s response to the initial treatments at the first interview and divided them into “responders” and “nonresponders”. Relapses were recorded. At the end of follow-up, each patient was evaluated and reclassified into “complete recovery” or “unhealed” groups. Intergroup differences were assessed. Results: All patients presented with seizures at the initial consultation. Other common manifestations included cognitive dysfunction (82.2%), psychiatric disturbance (66.7%), sleep disorder (54.5%), and hyponatremia (66.7%). During the follow-up period (32.8±13.5 months), six patients experienced relapse within 6-37 months. We observed that the patients who did not respond to the initial treatments and those who relapsed all had a poor long-term prognosis. The patients in the “unhealed” group were older (p=0.009), had a lower incidence of generalized tonic-clonic seizures (p=0.041), and had a higher probability of cerebrospinal fluid (CSF) abnormalities (p=0.024) than those in the “complete recovery” group. Conclusion: Anti-LGI1 encephalitis was characterized by seizures, cognitive impairment, psychiatric disturbance, and sleep disorders, and was often accompanied by hyponatremia. Patients who responded poorly to the initial treatments and those patients who relapsed had dismal long-term prognoses. Advanced age and CSF abnormalities may be risk factors for poor prognosis, but these still need to be verified.